Positron Emission Tomography - Juweid, Malik E.; Juweid, Malik E.; Hoekstra, Otto S.; Hoekstra, Otto S. (Methods in Molecular Biology, 2011)
Oncological imaging has thoroughly changed in the past decade, especially due to the introduction of PET and 18FDG. In Positron Emission Tomography, expert referring specialists and professional imagers seek to help bridge some of the knowledge gaps in several oncological domains.  The book’s goal is to aid in the improvement of communicative competences: to communicate scan findings so that the referring specialist receives proper advice from the imager, and that, alternatively, the referring one provides the imager with appropriate clinical details to allow for a proper interpretation, and that the referring specialist is aware of the possibilities and limitations of the requested technology. While it focuses on FDG PET, other radiopharmaceuticals are covered as well, where appropriate. Written for the highly respected Methods in Molecular Biology™ series, this volume provides the kind of detailed description and implementation advice that is crucial for getting optimal results.   Authoritative and convenient, Positron Emission Tomography serves as an excellent reference for oncologists, surgeons, radiotherapists, radiologists, nuclear medicine physicians, and pathologists desiring a stronger synergy within their vital efforts.